2016
DOI: 10.1007/jhep06(2016)178
|View full text |Cite
|
Sign up to set email alerts
|

Active Dirac neutrinos via SU(2) L doublets in 5d

Abstract: We propose a new mechanism to generate minuscule active neutrino masses in a five-dimensional (5d) spacetime of an interval without introducing SU(2) L singlet neutrinos. Under asymmetric boundary conditions on the two end points, a bulk mass for a 5d fermion allows a Dirac particle with a tiny mass eigenvalue. Implementing this mechanism, which provides us a new tool for building neutrino mass models, to the standard model gauge structure is possible when all the gauge bosons and the Higgs boson are localized… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 104 publications
1
5
0
Order By: Relevance
“…The results are in great agreement with experimental values [9,10] and for the mass of the Z boson M Z = 91.1876(21) GeV, when Q = M Z we obtain the value:…”
Section: Running Of the Fine Structure Constant And The Yukawa Couplingsupporting
confidence: 90%
“…The results are in great agreement with experimental values [9,10] and for the mass of the Z boson M Z = 91.1876(21) GeV, when Q = M Z we obtain the value:…”
Section: Running Of the Fine Structure Constant And The Yukawa Couplingsupporting
confidence: 90%
“…Finally, we reemphasize that it is quite difficult to understand why the Yukawa couplings of Dirac neutrinos are six orders of magnitude smaller than those of charged leptons, if they acquire their masses in the same way as in the SM. In this regard it has been shown that a relatively natural generation of tiny Dirac neutrino masses is not impossible in some models involving extra spacial dimensions [435,793,794,795,796], supersymmetry or stringy symmetries [199,797,798,799,800], radiative mechanisms [801,802,803,804,805] or some flavor symmetries [806,807,808,809,810,811,812,813]. That is why some attention has been paid to massive Dirac neutrinos and their phenomenological consequences.…”
Section: Model Building Based On a 4 Flavor Symmetrymentioning
confidence: 99%
“…It would, however, be of great interest to embed our setups into superstring theories. Although it is known that U (N ) gauge groups are hard to be obtained in 10D type II string theory with D-branes, our results will be still useful because some properties with respect to zero-mode wave functions, their degeneracies and Yukawa couplings induced by magnetic fluxes are the same as those even in cases of other gauge groups.2 Another attractive direction is considering various boundary conditions of fields on point interactions (zerothickness branes) in the bulk space of a five-dimensional theory on S 1 (or a line segment)[47][48][49][50].3 Note that only T 2 -related cases were discussed in[61]. But, addressing other higher-dimensional tori is possible in principle in a similar method.…”
mentioning
confidence: 89%